Pengaruh Fintech Pembayaran dan Literasi Keuangan terhadap Perilaku Konsumtif dengan Perilaku Pengelolaan Keuangan Pribadi sebagai Variabel Intervening pada Mahasiswa UPI YPTK Padang - Fajri Rahmi; Elfiswandi Elfiswandi; Rindy Citra Dewi (Lembaga Yasin AlSys, 2026)
Research on payment financial technology (fintech) and financial literacy in relation to students’ consumptive behavior has been widely conducted; however, studies that specifically examine the role of personal financial management behavior as an intervening variable in the context of UPI YPTK Padang students remain limited. This study aimed to analyze the influence of payment fintech and financial literacy on consumptive behavior, with personal financial management behavior as an intervening variable. A quantitative approach with a survey design was employed involving 100 respondents selected using proportionate stratified random sampling based on Slovin’s formula. Data were collected through questionnaires that had been tested for validity and reliability, and were then analyzed using multiple linear regression and path analysis with the assistance of SPSS. The results showed that payment fintech and financial literacy had a positive and significant effect on personal financial management behavior, and that payment fintech had a positive and significant effect on consumptive behavior. Conversely, financial literacy and personal financial management behavior did not have a significant effect on consumptive behavior, so the indirect effect through the intervening variable was also not proven to be significant. These findings enrich the literature on financial behaviour in digital transactions and suggest that universities integrate financial literacy education with the strengthening of digital spending control in order to guide students’ consumptive behavior toward more rational patterns.